1975
DOI: 10.1080/00288233.1975.10421017
|View full text |Cite
|
Sign up to set email alerts
|

Effect of soil fumigation on white clover growth in a yellow-grey earth infested with clover cyst nematode

Abstract: A field trial to study the effects of soil fumigants on pure swards of 'Grasslands Huia' white clover growing in a yellow-grey earth infested with clover cyst nematode (Heterodera irijolii) , was run for 18 months. The treatments, replicated four times (24 plots, 2 x 1 m), were: control, methyl bromide, 'DD' soil fumigant at 300 l/ha, 'Nemagon' at 11.23 l/ha. 'Nemagon' at 22.46 l/ha, and 'Mocap' at 67 kg/ha. Twelve harvests were made during the trial and mean yield response to fumigation was 7.6% [-0.2% ('Nema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

1975
1975
2008
2008

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 4 publications
0
14
0
1
Order By: Relevance
“…Pot and field trials reported by Yeates (1974) and Yeates et al (1975) have given some indication of the effects of H. triiolii on dry matter production; cognizance, however, must be taken of secondary effects and the role of nematodes in plant disease complexes (Wallace 1973). No attempt is made here to assess the impact of the changed nematode populations on pasture production.…”
Section: Ecological Relationshipsmentioning
confidence: 99%
“…Pot and field trials reported by Yeates (1974) and Yeates et al (1975) have given some indication of the effects of H. triiolii on dry matter production; cognizance, however, must be taken of secondary effects and the role of nematodes in plant disease complexes (Wallace 1973). No attempt is made here to assess the impact of the changed nematode populations on pasture production.…”
Section: Ecological Relationshipsmentioning
confidence: 99%
“…Responses of 10% in white clover and 13% in total dry matter yields found in mixed pasture under grazing management are of the same order as those obtained in ungrazed pure stands of white clover (Yeates et al 1975a(Yeates et al , 1975b. Apparently, under grazing management the movement of stock over an l l-month period did not eliminate the differences, although the greater powers of infestation by H. triiolii are evident.…”
Section: Days After Sowingmentioning
confidence: 53%
“…Trials using pure swards of white clover have shown responses to fumigation of 7-12% in a yellow-grey earth containing H. triiolii (Yeates et al 1975a), and of 6-15% in a yellow-brown loam containing both H. trijolii and M. hapla (Yeates et al 1975b). Responses of 10% in white clover and 13% in total dry matter yields found in mixed pasture under grazing management are of the same order as those obtained in ungrazed pure stands of white clover (Yeates et al 1975a(Yeates et al , 1975b.…”
Section: Days After Sowingmentioning
confidence: 70%
“…The clover cyst nematode {Heterodera trifolii Goffart) occurs throughout New Zealand (Skipp & A96057 Received 26 July 1996;accepted 19 December 1996 Christensen 1983; Mercer & Woodfield 1986) and causes a general root malfunction and accompanying depression of foliage growth in white clover (Trifolium repens L.) (Taha & Raski 1969;Widdowson et al 1973;Yeates et al 1975). Field trials in the United States measured reductions of 14 and 46% for two lines of white clover (Norton 1967).…”
Section: Introductionmentioning
confidence: 99%